The Relationship Between Locus of Control and Entrepreneurship - DEMIRTAS, Ozgur; KARACA, Mustafa (International Journal of Business Strategy and Social Sciences, 2017)
In this study, we examined and drew attention to the entrepreneurial characteristics of students who were potentially at the beginning of an entrepreneurial process. Furthermore, we have analyzed the entrepreneurship literature to develop an understanding of the cultural dimensions that may have an impact on entrepreneurial process. A sample of students was selected as the study participants in the provinces of Kayseri and Yozgat. The data was collected employing face to face interviews. The results have indicated that culture has an impact on entrepreneurship and locus of control.